Struktury zarządzania w gospodarstwach indywidualnych na kluczowych rynkach rolnych w Polsce - Czyżewski, Bazyli (Governance Structures in the Family Farms on Main Agricultural Markets in Poland, 2006)
The contractual integration determines a rise in competitiveness of Polish agricultural sector. According to neo-institutional methodology, the author proposes a typology of governance structures on a milk, hogs and grain market. There is also an attempt to verify the thesis that a higher level of hierarchy in Polish individual farms implies an increase of added value.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 168-172